Illocutionary Act in Political Debate - Khodijah, Siti (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2020)
This study analyzes illocutionary act in political debate that was conducted by general election commision on March, 30 2019. This debate was about ideology, government, security and defense, and international relationship. In this research, Searle’s theory was used who classified five types of illocutionary act; representative, directive, commisive, expressive, and declarative. This research used descriptive qualitative. The main focus of this study is to get deep understanding and interpretation how the politicians argue each other using illocutionary act. The results of this study suggested that both of the candidates of president did not use all of the illocutionary act types proposed by Searle. The three illocutionary acts used by both of the candidates are, representative, directive, commissive. Meanwhile, another type of illocutionary acts used by one of the candidates is declarative, while another one used expressive.